UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN PENERAPAN METODE QIROAH PADA PELAJARAN BAHASA ARAB KELAS VIII SEMESTER GANJIL MTs PGRI I LABUHAN RATU LAMPUNG TIMUR TAHUN AJARAN 2009/2010: UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN PENERAPAN METODE QIROAH PADA PELAJARAN BAHASA ARAB - Ahmad Romdhoni; Muhammad Zaky Sya’bani (An Naba, 2018)
Arabic lessons taught at school function as the language of religion and science, as well as means of communication. Based on observations and interviews with Arabic teachers in MTs PGRI I Labuhan Ratu Lampung Timur, it was obtained that the learning outcomes of Arabic in class VIII were still low at 36.86 far from the predetermined mastery value of the school which was 60.00. By doing Qiroah, students can immediately see the writing, recite, listen and at the same time, they look for the meaning of a word or sentence. The purpose of this study is to describe the learning activities of Arabic, describe the results of learning Arabic and describe the activities of teachers in using the Qiroah method. This study was conducted in class VIII of MTs PGRI I Labuhan Ratu Lampung Timur in the 2009/2010 school year with a total of 28 students consisting of 15 male students and 13 female students. Data obtained through student activity observation sheets, teacher activity observation sheets, and written examinations. In this study, the average student learning outcomes in cycle 1 were 51.36, cycle 2 53.98, cycle 3 62.96. The results of student activity data in accordance with the learning objectives (On Task) cycle 1 of 57.55, cycle 2 62.73, cycle 3 64.29. While the percentage of assessment results obtained from the accompanying teacher for teacher activities obtained data as follows cycle 1 of 82.79%, cycle 2 88.57, cycle 3 92.37.